Determination of the sensitized zone extension in welded AISI 304 stainless steel using non-destructive electrochemical techniques - Lima Neto, Pedro de (2008)
Extension of sensitized zone (SZ) in welded AISI 304 stainless steel was determined by two non-destructive electrochemical tests: double loop electrochemical potentiokinetic reactivation technique (DLEPR) and local electrochemical impedance spectroscopy (LEIS). Welding was carried out using the shielded metal arc with two selected welding energies: the first one (0.7kJmm¡1) does not promote the sensitization of the 304 steel and it constitutes the reference sample and the second one (2.2kJmm¡1) which leads to the precipitation of chromium carbides in the grain boundaries after the welding process. The non-destructive DLEPR and LEIS tests allowed the length of the SZ to be determined and a good agreement between the two techniques and the microstructure of the two welded samples was shown. The presence of an inductive loop on the local impedance diagrams seems to reflect a galvanic coupling between the weld string (anode) and the welded stainless steel plates (cathode) which will be very prejudicial to a good corrosion resistance of the welded system. The results showed that the two electrochemical tests could be applied in practical cases in industrial field.